1987
DOI: 10.1364/josaa.4.000519
|View full text |Cite
|
Sign up to set email alerts
|

Low-dimensional procedure for the characterization of human faces

Abstract: A method is presented for the representation of (pictures of) faces. Within a specified framework the representation is ideal. This results in the characterization of a face, to within an error bound, by a relatively low-dimensional vector. The method is illustrated in detail by the use of an ensemble of pictures taken for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
896
0
22

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,921 publications
(922 citation statements)
references
References 2 publications
4
896
0
22
Order By: Relevance
“…Although statistical face modelling started earlier (see for example [32]), [28] is widely regarded as the inauguration of face modelling. The model is built from a set of k 2D frontal images.…”
Section: Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although statistical face modelling started earlier (see for example [32]), [28] is widely regarded as the inauguration of face modelling. The model is built from a set of k 2D frontal images.…”
Section: Modelsmentioning
confidence: 99%
“…Whether in 2D (eye-centre-aligned [32] or shape-free, warped images [73]) or 3D (depth maps [74], fields of surface normals [17] or meshes in dense correspondence [9]), human faces have been shown to be highly amenable to description using a linear statistical model. 2D approaches model appearance directly, with the training data capturing both extrinsic scene properties (such as illumination and camera parameters) and intrinsic face properties (geometry and reflectance properties).…”
Section: State Of the Artmentioning
confidence: 99%
“…It reduces the dimensionality of the description by projecting the points onto the principal axes, where orthonormal set of points are in the direction of maximum covariance of the data. PCA is an optimal compression scheme that minimizes the mean squared error between the original images and their reconstructions for any given level of compression [23,24]. works by finding a new coordinate system for a set of data, where the axes (or principal components) are ordered by the variance contained within the training data [25].The approach for face recognition aims is decompose face images into small set of characteristic feature images called eigenfaces which used to represent both existing and new faces.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…Sirovich and Kirby [8,9] evaluated a limited version of this framework on an ensemble of 115 images (M = 115) images of Caucasian males digitized in a controlled manner, and found that 40 eigenfaces were sufficient for a very good description of face images. In practice, a smaller M' can be sufficient for identification, since accurate reconstruction of the image is not a requirement.…”
Section: Using Eigenfaces To Classify a Face Imagementioning
confidence: 99%